Complementary and alternative medicine use among infertile women attending infertility specialty clinics in South Korea: does perceived severity matter? - Jung Hye Hwang; Yi Young Kim; Hyea Bin Im; Dongwoon Han (BMC, 2019)
Abstract Background Complementary and alternative medicine (CAM) use among infertile women is popular in many countries, including Korea. Previous research has repeatedly found more than half of infertile women surveyed use CAM therapies for fertility enhancement and overall well-being. However, there is currently little evidence to support this practice, and this raises the question of infertile women's experiences in the uptake of those modalities and sociodemographic and psychological factors associated with CAM use. Thus, this study aims to explore the perceptions and experiences of infertile women with regard to their use of CAM in Korea. Methods A cross-sectional study was conducted using data from 263 infertile women attending infertility specialty clinics in Seoul, Korea, in June 2012. The survey instrument included 47 questions on the use of CAM, demographic characteristics, health status, and infertility related factors such as duration and type of infertility, experience and satisfaction of conventional treatment, and self-perceived severity of infertility condition. Chi-square test and logistic regression were used for data analysis. Results Among 286 respondents (response rate, 95.3%), a total of 263 women were included in the final analysis. 63.5% of respondents used one or more types of CAM modalities during infertility treatment. The utilization of CAM was associated with employment status, duration of infertility treatment, and self-perceived severity of the disease. The most commonly used CAM modalities were multivitamin and herbal medicine, and differences in types of CAM modalities used were found between the group with a higher rating of self-perceived disease severity and the lower perceived severity group. Conclusions High prevalence of CAM use among infertile women was observed in Korea. Our findings support that infertile women's own understanding of their illness and physical condition influences self-care behavior such as CAM use. This calls for an urgent need for further in-depth study of the clinical effects of popular CAM modalities among infertile women when used in conjunction with conventional treatment.